SISTEM PENDUKUNG KEPUTUSAN PROGRAM KELUARGA HARAPAN (PKH) MENGGUNAKAN METODE MEREC dan SIMPLE ADDITIVE WEIGHTING (SAW) - ilyas daeng (PT. ZIVANA CENDEKIAWAN BANGSA, 2026)
The Family Hope Programme (PKH) is one of the Indonesian government's social assistance programmes aimed at alleviating poverty and improving community access to education, health and social welfare services. However, at the village level, the process of determining PKH recipients is often still carried out manually and subjectively, which has the potential to lead to inaccuracies in targeting. This study aims to determine the priority of PKH recipients in Kuala Lahang Village, Gaung Subdistrict, Indragiri Hilir Regency, using a Decision Support System approach through a combination o*f the Method based on the Removal Effects of Criteria (MEREC) and Simple Additive Weighting (SAW) methods. The MEREC method is used to determine the weight of criteria objectively based on the removal effect of criteria, while the SAW method is used to calculate preference values and rank alternatives. This research is applied research with a quantitative approach, where data is obtained through interviews and documentation. The results of the study indicate that the combination of the MEREC and SAW methods is capable of producing a more objective, transparent, and measurable ranking of PKH recipient candidates, which can be used as a basis for decision-making in determining PKH aid recipients.